2017
DOI: 10.21660/2017.30.96545
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Paclobutrazol Concentrations and Time of Foliar Application on Flowering of ‘Namdokmai-Sitong’ Mango

Abstract: Paclobutrazol (PBZ) is a growth regulator used to control vegetative growth, stimulating the reproductive capacity of plants. PBZ has been widely marketed throughout the tropics to stimulate mango flowering. In the recent years, many reports showed that application of PBZ by soil drenching can cause permanent stunting of flushes, the vegetative and root growth of mango was reduced. The aim of this work was to determine the effects of PBZ on flowering of mango by foliar application. The commercial mango cultiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…1) [23,38,39]. As a result, it decreases vigour and promotes floral induction and development [9,10,15].…”
Section: Strigol Strigyl Acetate and Sorgolactonementioning
confidence: 99%
See 2 more Smart Citations
“…1) [23,38,39]. As a result, it decreases vigour and promotes floral induction and development [9,10,15].…”
Section: Strigol Strigyl Acetate and Sorgolactonementioning
confidence: 99%
“…Authors such as Barman et al [44] in a research on mango (Mangifera indica L.) "Dashehari" applied 3.2 mL m 2 of PBZ in the month of September; they reported a significant increase in flowering and 30% more yield. In another experiment, but with the variety "Namdokmai-sitong", the application was carried out 15 and 45 days after pruning with doses of 500, 1000, 1500 and 2000 mg L -1 , which resulted in a decrease in vegetative growth and an improvement in the number of flowers and buds [10]. On the other hand, in Brazil, Do Amaral Brogio et al [15] carried out foliar applications of PBZ (1750 mg L -1 ) on avocado (Persea americana L.) "Hass" and found that it modified the shape of the fruit and caused a significant increase in fruit size.…”
Section: Use Of Pbz In Fruit Treesmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that GAI is a repressor of GA responses and inhibits the expression of LFY, the results of GAI being up-regulated in three times points and its repressor (RGA) being down-regulated in four times points imply that GA inhibitors such as paclobutrazol (PBZ) can be applied to induce early cone formation in D. pectinatum. After all, PBZ has been found effective in early flowering in several woody species such as camellias, apple, and mango [47][48][49][50][51].…”
Section: Gene Expression Is Modulated During D Pectinatum Male Cone D...mentioning
confidence: 99%
“…The dose and form of application also influence the response of plants to PBZ [5,7,8]. In this case, the challenge has been to identify the appropriate dose and method of application [5,9], since an overdose can cause undesirable effects, such as growth delay, panicle malformation and reduction in the vegetative and root growth of mango trees [10].…”
Section: Introductionmentioning
confidence: 99%